A study on the application of artificial neural network to predict k-eff and peaking factor of a small modular PWR - Le , Tran Chung; Nguyen , Thi Dung; Tran, Tran Viet Phu (Nuclear Science and Technology, 2026)
Machine learning (ML) using artificial neural network (ANN) methods is being applied to predict required parameters for nuclear reactors based on learning from big data sets. The ML models usually give faster calculation speed while the accuracy is good agreement with physical simulators. In this work, a multi-layer perceptron network was built and trained to predict k-eff and peaking factor of a small modular pressurized water reactor (PWR). The results are compared with those obtained by using a reactor physics code system, i.e. SRAC2006. The comparison shows good agreement accuracy and higher performance of the ML models.